1996
DOI: 10.1104/pp.112.2.575
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Symbiotic N2 Fixation in Trifolium repens L. under Elevated Atmospheric pCO2 in a Grassland Ecosystem

Abstract: ~Symbiotic N, fixation is one of the main processes that introduces N into terrestrial ecosystems. As such, it may be crucial for the sequestration of the extra C available in a world of continuously increasing atmospheric CO, partial pressure (pC0,). The effect of elevated pC0, (60 Pa) on symbiotic N, fixation ('5N-isotope dilution method) was investigated using Free-Air-C0,-Enrichment technology over a period of 3 years. Trifolium repens was cultivated either alone or together with Lolium perenne (a nonfixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
161
2
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(179 citation statements)
references
References 38 publications
(59 reference statements)
15
161
2
1
Order By: Relevance
“…In this study, we focused on L. perenne and T. repens mainly to compare our data with other studies performed on the FACE field experiment in Eschikon (Switzerland) [23,25,29,30,42,57,72,74]. Moreover, the plants have different rhizosphere structures.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In this study, we focused on L. perenne and T. repens mainly to compare our data with other studies performed on the FACE field experiment in Eschikon (Switzerland) [23,25,29,30,42,57,72,74]. Moreover, the plants have different rhizosphere structures.…”
Section: Discussionmentioning
confidence: 98%
“…These authors showed in the rhizosphere of T. repens a twofold increase in R. leguminosarum counts in samples retrieved in May and in November. Moreover, in the same FACE study site, Zanetti et al [74] showed that total N yield increased significantly in T. repens under elevated CO 2 and was assigned to an increased formation of nodules [73].…”
Section: Impact Of Elevated Co 2 On Heterotrophic Bacteria In the Rhimentioning
confidence: 94%
See 3 more Smart Citations